A técnica dos quantis como ferramenta para classificar os anos em secos, muito secos, normais, úmidos e muito úmidos para o Estado do Rio Grande do Sul - Moreira, Aires Carpinter (2003)
The pluviometric precipitation is of fundamental importance for the several human activities, for that reason, more and more, it has been studied and used in several areas of the knowledge. Due to its importance, this work aims at enriching the information on the subject, through the use of the QuantisTechnique Quantis in 20 weather stations in the State of Rio Grande do Sul. The objectives are: to classify the years in very dry, dry, normal, humid and very humid, to analyze the series of pluviometric precipitation between the period of 1913-1998, to calculate limits values for the percentiles previously determined, to show and to discuss the space distribution, to calculate the probability of occurrence of extreme values and to verify the influence of the El Niño and La Niña weather phenomena on the observed precipitation. For the period studied, 86 years, the Quantis Technique demonstrated being a solid tool reach the objetives proposed in this work. The obtained results showed that the pluviometric precipitation in the State of Rio Grande do Sul is well distributed not being noticed extreme values of significant relevance. The total absolute montly maximum precipitation varied from 393,3 mm (Tapes) to 861,0 mm (Santa Maria) having April as a unique month; for the total absolute monthly minimum, the variation happens in the interval of 0,3 mm monthly (Bento Gonçalves). The Quantis Technique enables classifying the years in very dry, dry, normal, humid and very humid. In general way, 50% of the years studied (43 years) are classified as normal; 20,7% are considered dry, in other words, approximately 18 years; 14,3 years are considered humid (12,3 years); 10,23% are in the very humid range (8,8 years) and only 4,8%, of the 86 years, are very dry (4,1 years). In relation to the influence of the El Niño and La Niña events the results showed that most of the stations are considered as normal, not having been noticed extreme classifications as very dry, for example. Despite the fact that the State of Rio Grande do Sul is located in an area where the El Niño and La Niña events are relevant, it has been noticed in some years no occurrence of the phenomena, being therefore denominatedneutral years.